Analysis of Centroid Trajectory Characteristics of Axial-Flow Pump Impeller Under Hydraulic Excitation - Duan, Xiaohui; Tang, Fangpin; Xu, Hao; Chen, Jian; Lu, Qun; Duan, Wenyong; Zhang, Rentian (Frontiers in Energy Research, 2021)
The hydraulic excitation characteristics of axial flow pump unit are studied through theoretical analysis, numerical simulation and field test in this paper. The correlation between impeller hydraulic and radial vibration displacement of impeller centroid is obtained through theoretical analysis. Through the 1-way fluid-solid-interaction(FSI)numerical simulation, the distributions of water pressure and displacement on the impeller surface are obtained, and the time-domain and frequency-domain characteristics of transient hydraulic and radial displacement are revealed. Through the field test, the external characteristics of axial flow pump unit and the time-frequency characteristics of the pressure pulsation at the measuring points beside the inlet of the impeller are obtained. The comparisons between simulation results and experimental results show that the former is accurate and reliable.